Molecular Docking of Flavan-3-Ol Compounds from Cocoa Beans Againts Matrix Metalloproteinases (MMPs) as Anti-Photoaging Agents - Cindi Dia Annisa; Widji Soeratri; A'liyatur Rosyidah, M.Si., Ph.D; Tristiana Erawati (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Premature aging of the skin is an abnormal aging process that is primarily triggered by UV exposure, which leads to increased production of matrix metalloproteinases (MMPs). These enzymes degrade skin collagen. The abundant flavan-3-ol content of cocoa beans has been demonstrated to possess antioxidant properties, thereby serving as a potential agent to impede premature aging. A molecular docking approach can facilitate the prediction of cocoa bean flavan-3-ols' capacity to impede MMP enzyme activity. Objective: This study aims to predict the interaction between cocoa bean flavan-3-ol compounds and MMP enzymes as potential photoaging inhibitors. Methods: Flavan-3-ol compounds from cocoa beans, including (-)-epicatechin, (+)-catechin, procyanidin B1, B2, and C1 were obtained from PubChem and modeled in 3D using ChemDraw 3D software. These compounds were docked into the collagenase (MMP-1), stromelysin (MMP-3), and gelatinase (MMP-9). The docking results were compared to native ligands of the proteins. AutoDock was used for docking, and the results were visualized using Biovia Discovery Studio. Results: Method validation confirmed that all proteins were suitable for docking. The docking results showed negative docking scores for all compounds, with each compound binding at least one amino acid residue similar to native ligands. Procyanidin B2 exhibited the best docking score and the smallest inhibition constant for collagenase and gelatinase 9. Conclusion: Cocoa bean flavan-3-ol compounds can inhibit collagenase, stromelysin, and gelatinase activity. Procyanidin B2 is the most effective compound among those tested. Consequently, further testing may be undertaken to generate supporting evidence for potential utilization of cocoa beans as an active compound in cosmetic formulations.